2020
DOI: 10.1186/s13048-020-00754-0
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: LncRNA CTBP1-AS2 sponges miR-216a to upregulate PTEN and suppress endometrial cancer cell invasion and migration

Abstract: This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13048-020-00754-0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…PTEN can dephosphorylate PIP3 and maintain PIP3 at a low level, thereby down-regulating the PI3K/AKT pathway ( Carnero et al, 2008 ). Studies have shown that mutation or deletion of PTEN can increase the proliferation, migration, invasion and cisplatin resistance of endometrial cancer cells ( Chen et al, 2018 ; Wang et al, 2020 ). PTEN is the most frequently mutated gene in endometrial cancer and has the highest mutation rate in endometrioid adenocarcinomas, but mutations in serous carcinomas are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN can dephosphorylate PIP3 and maintain PIP3 at a low level, thereby down-regulating the PI3K/AKT pathway ( Carnero et al, 2008 ). Studies have shown that mutation or deletion of PTEN can increase the proliferation, migration, invasion and cisplatin resistance of endometrial cancer cells ( Chen et al, 2018 ; Wang et al, 2020 ). PTEN is the most frequently mutated gene in endometrial cancer and has the highest mutation rate in endometrioid adenocarcinomas, but mutations in serous carcinomas are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN mutation is the most frequent type of mutation in EC [13]. Tumor suppressor PTEN has been shown to interact with cell adhesion complexes and stabilize cell junctions, thereby reducing invasion and metastasis of a range of cancer cells including EC [14][15][16]. Previous studies have been keen to investigate the in uence of PTEN mutation on the progression and prognosis of endometrial cancer, but few focused on the development of PTEN mutational status associated prognostic signature [17][18][19].…”
Section: Discussionmentioning
confidence: 99%